ANALISIS PERBEDAAN TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN RAWAT JALAN DI PUSKESMAS HALMAHERA DAN PUSKESMAS TLOGOSARI WETAN KOTA SEMARANG TAHUN 2016 - Melodi Damai Soleiman; Putri Asmita Wigati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Primary health care is one of public care facilities where in charge of operating health care to public which forced to increase performance quality and quality for providing care. Outpatient is one of the services provided by the health centers. Halmahera Health Care (Certified by ISO) was generally complained about long queing time and care procedure disclosure and also implementation care declaration.  The aim of this research was to determine differentiation between public satisfication level among Halmahera Primary Health Care (Certified by ISO) and Tlogosari Wetan (Uncertified by ISO). This research was using descriptive model with public satisfication index. The result of data was number with different test with Mann-Whitney test. The Data showed that public satisfication index number in Halmahera Primary Health Care was 75,63 and Tlogosari Wetan was 73,52 or simply classified in good quality services. There was no significant differences between patient satisfication level, except condition care elements, care procedures, time services, and care declaration. Statistic analysis showed that there was differentiation between satisfication level among four of care elements (p = 0.000). While for cost (p=0.155), specification product of services type (p=0.728), competency and operator behavior (p=1.000), complaint handling, suggestion, and recommendation (p=0.317). Halmahera primary health care as primary health care where already certified by ISO is categorized into good performance primary health care according to public satisfication level.The recommendation to Primary health care is to improve and increase quality, so that care quality and public satisfication will be enhancement.